Survivable virtual topology search with impairment awareness and power economy in optical WDM networks. (4th May 2020) - Pandya, Rahul Jashvantbhai
Survivability against the link and light-path failures is essential in the optical wavelength division multiplexing (WDM) network along with impairment awareness (IA) and power economy (PE). In this paper, topology search using: 1) Kruskal's minimal weighted topology search algorithm; 2) Hamiltonian cycle (H-cycle)-based survivable topology search algorithm; 3) k-survivable topologies search algorithms have been carried out to find virtual survivable topologies for India's RailTel network. The integer linear programming (ILP) optimisation followed by the heuristics implementation have been carried out for IA and PE with a channel capacity constraint to achieve the survivability considering the case of a single link and light-path failures. We compare the survivable topologies thus obtained in the event of failures, with respect to terminal-to-terminal (terminal) reliability and choose the survivable topologies having the better terminal reliability. Among all, H-cycle-based survivable topology search algorithm shows lowest connection loss probability (CLP) and highest terminal reliability.